Sources of organizational stress among youth rhythmic gymnasts an interpretative phenomenological analysis - Penna, E. M.; Filho, E.; Bentes, L. M. N.; Ferreira, R. M.; Pires, D. A. (Science of Gymnastics Journal, 2023)
The aim of the study was to explore sources of organizational stress among Brazilian youth rhythmic gymnasts. Semi-structured interviews were conducted with six female athletes aged approximately 15 years (M = 14.50; SD = 1.76) with approximately seven years of experience in the sport on average (M = 6.83; SD = 3.25). Deductive categorical analysis was used to analyze the raw data. Our analysis revealed that sport entrapment, time management, and body image concerns are some of the stressors experienced by rhythmic gymnasts. Coach-pressure, peer-pressure, and parental-pressure are additional sources of stress reported by the athletes. Finally, the athletes reported experiencing competitive anxiety before, during, and after competition. Collectively, our findings suggest that rhythmic gymnasts reported a multitude of sport-related stressors. To counter these pressures, coaches, and practitioners need to equip athletes with a variety of coping skills in order to promote well-being and increase peak performance in the sport.